Increased β‐endorphin and autotaxin in patients with prurigo - Takahiro Ishikawa; Takashi Hashimoto; Takichi Munetsugu; Hiroo Yokozeki; Takahiro Satoh (Frontiers Media S.A., 2019)
Abstract Objectives Prurigo is a treatment‐resistant inflammatory disease of unknown etiology. Persistent and severe itch is a major and important clinical symptom, but pathological mechanisms and/or actual mediators for itch in prurigo remain to be defined. Methods We investigated blood levels of β‐endorphin, dynorphin A, and autotaxin in adult patients with prurigo (n = 18), including prurigo nodularis, prurigo chronica multiformis, and other forms. Patients with hemodialysis, hepatic dysfunction, and pregnancy were excluded. Immunofluorescence staining for β‐endorphin and autotaxin in lesional skin was also performed. In addition, β‐endorphin and autotaxin synthesis of cultured epidermal keratinocytes in response to several cytokine stimulation was assessed in vitro. Results Blood levels of β‐endorphin were higher in patients with prurigo than in control subjects (n = 20), while dynorphin A levels were comparable in the two groups. Blood autotaxin levels also were increased in patients with prurigo compared to control subjects. On the one hand, epidermal expression of β‐endorphin was increased in skin lesions of prurigo chronica multiformis, but not in prurigo nodularis. On the other hand, enhanced expression of autotaxin was observed in the epidermis in both prurigo nodularis and prurigo chronica multiformis. In vitro studies showed that β‐endorphin‐expressing epidermal keratinocytes increased following stimulation with TNF‐α, interleukin‐31, and/or IFN‐γ. Autotaxin was also detected in the cytoplasm of cultured epidermal keratinocytes. The fraction of autotaxin‐expressing cells increased when stimulated with TNF‐α and/or interleukin‐31. Conclusions Imbalance of opioid receptor signals and/or the autotaxin‐lysophosphatidic acid axis may contribute, at least in part, to the pathogenesis and intractable pruritus in some of the patients with prurigo.